Predicting the crack initiation fracture toughness for a crack along the bimaterial interface - Shah, Qasim Hussain; Azram, Mohammad; Iliyas, M. H. (Asian Network for Scientific Information, 2005)
Three Point Bend (3PB) bimaterial specimens of PMMA/PC were made by joining the two materials using friction welding. The specimens were tested and the crack initiation loads were recorded to evaluate the K using ASTM standard E 1820-01. Stress field in the crack tip vicinity was studied using finite element IC analysis of the specimen model. Normal and shear stresses were recorded for a series of nodes ahead of the crack tip at (2=0°). SIF values were calculated using these stress values and it was found that the stresses at a certain distance lying outside the process zone provide a SIF value matching to that of experimental fracture toughness of the specimen under study. Based upon the experimental evidence and finite element analysis, a simple step by step procedure is proposed to calculate the fracture toughness of bimaterials for a complex stress field.